Aelfric and the cult of saints in late Anglo-Saxon England - Gretsch, Mechthild (Cambridge studies in Anglo-Saxon England, 2005)
The cult of saints was one of the most important aspects of life in the Middle Ages, and it often formed the nucleus of developing group identities in a town, a province or a country. The literature of Anglo-Saxon England is unique among contemporary European literatures in that it features a vast amount of saints' Lives in the vernacular. Of these Lives, Ælfric is the most important author, and his saints' Lives have never previously been explored in their contemporary setting. In this study, Gretsch analyses Ælfric's Lives of five important saints in the light of their cults in Anglo-Saxon England. This gives the reader fascinating glimpses of 'Ælfric at work': he adapts the cults and rewrites the received Latin hagiography of the five saints, with the result that each of their English Lives conveys a distinct message to the contemporary political elite and to a lay audience at large.